SHOPPING PERFORMANCE ANALYSIS IN THE REPORT OF BUDGET REALIZATION BEFORE AND DURING PANDEMIC AT THE SOCIAL SERVICES OF MAGELANG CITY - Esti Aulia Fahlul Laily (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
The Budget Realization Report (LRA) published by local governments provides very useful information for assessing regional financial performance. LRA is one of the most important regional financial accountability reports. Based on the LRA. the reader of the report can analyze the performance of financial statements in the form of income analysis, expenditure analysis and financing analysis. The objective of this study was to determine and analyze the performance of spending in the budget realization report (LRA) of the Magelang City Social Service. The analytical methods used are: analysis of spending variance, analysis of spending growth, analysis of shopping compatibility and analysis of spending efficiency. Based on the results of the analysis that has been carried out, it can be concluded the proposed hypothesis is rejected because spending performance declined in 2020, which is as evidenced by 1) in 2020 the number budget of 3.583.423.000 and realization of expenditure of 3.339.361.981 decreased in 2019 with a budget of 6.275.307.000 and its realization 5.599.423.671; 2) the variance of spending in 2020 is lower than in 2019; and 3) spending growth ratio in 2020 decreased by 6.8108347521.